The Impoliteness of Slurs in Debt Collectors' Conversation to Online Debtors - Hanif, Anisah; Djatmika; Santosa, Riyadi; Sumarlam (International Proceedings of Nusantara Raya, 2023)
The phenomenon of impoltiness act penetrates in all areas of work. It happens because almost jobs involve power, so the level of persins's power affecct a person's chances for commiting slurs impoliteness towards someone with power below them indirectly in study. Online loans used as a sure-fire way to deal with fast financial problems and an easy transaction process, so many people are temted. It will be the worst consequences if the right lens to see this language phenomenon, because it cannot be debt collectors to their online debtor.